RANCANG BANGUN ALAT BANTU KERJA PENGEMASAN GAS BIO KE DALAM TABUNG MELON - Samsuri, Moh.; ., Asmungi (Heuristic, 2017)
There has been a lot of biogas packaging done by the community, but so far there are many weaknesses in it so there needs to be further research. This research is intended to ergonimically design a working tool for packaging of bio gas into melon tubes. Using the Nordic body map and measuring the fatigue level, a manual ergonomically shaped work auxiliary device has been proven to be safe, comfortable and painless for the user. To fully fill the melon tube requires only 115 pumps with an average fatigue level of 15.1% (not exhausting).Keywords: work aid tool, biogas, melon tube